Efficacious nitrogen introduction into MoS2 as bifunctional electrocatalysts for long-life Li-O2 batteries. (10th February 2021) - Fan, Xiaoping; Huang, Youguo; Wang, Hongqiang; Zheng, Fenghua; Tan, Chunlei; Li, Yu; Lu, Xifei; Ma, Zhaoling; Li, Qingyu
Highlights: The porous flower-like structure of N-MoS2 was prepared via a facile two-step procedure. The doping of N atoms induce Mo-N bonds and a large number of sulfur vacancy to enhance the catalytic activity for ORR and OER of MoS2 . The Li-O2 battery with N-MoS2 as the cathode catalyst exhibits an excellent cycling stability of 224 cycles. Abstract: Defect engineering has been an efficient means to govern the electrocatalytic performances of oxygen electrode in Li-O2 batteries. Herein, we introduce N atoms into MoS2 for manufacturing sulfur vacancies to improve the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) kinetics of rechargeable Li-O2 batteries. The obtained results show that N doping opened the crystal distance space of N-MoS2, reduced the charge transfer resistance and simultaneously induces Mo-N bonds and a large number of sulfur vacancies. The assembled Li-O2 batteries with N-MoS2 as the cathode electrocatalyst deliver discharge specific capacity of 5205.5 mAh g −1 at the current density of 100 mA g −1, which is much higher than the MoS2 (2600.3 mAh g −1 ). It also shows excellent cyclic performance with 224 cycles at the current density of 200 mA g −1 within a capacity limitation of 1000 mAh g −1 . Overall, the as-developed N-MoS2 could be regarded as a promising cathode electrocatalyst for Li-O2 batteries. Graphical abstract: Image, graphical abstract